Cancer does not stop Amira from achieving success, receives University Gold Award - Siti Nurfarmy, Ibrahim (2022)
PAYA BESAR, 6 August 2022 – When it was confirmed that she had muscle tissue cancer or rhabdomyosarcoma in the early semester of her study, Amira Abdul Talib, 29, felt that it had increased the burden on the family.